2014
DOI: 10.1103/physreva.89.032303
|View full text |Cite
|
Sign up to set email alerts
|

Feed-forward control for quantum state protection against decoherence

Abstract: We propose a novel scheme of feed-forward control and its reversal for protecting quantum state against decoherence. Before the noise channel our pre-weak measurement and feed-forward are just to change the protected state into the state almost immune to the noise channel, and after the channel our reversed operations and post-weak measurements are just to restore the protected state. Unlike most previous state protection schemes, ours only concerns the noise channel and does not care about the protected state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 39 publications
(71 reference statements)
2
35
0
Order By: Relevance
“…This is not the case at least for the amplitude damping noise, e.g. spontaneous emission; it is shown numerically that there exists a quantum protocol that can do better than the "do nothing" and "discriminate & reprepare" protocols [12]. Our result suggests that noise suppression for completely unknown input states is impossible except by using the bias or anisotropy of the noise itself even when one includes the ex-ante control in the scheme.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…This is not the case at least for the amplitude damping noise, e.g. spontaneous emission; it is shown numerically that there exists a quantum protocol that can do better than the "do nothing" and "discriminate & reprepare" protocols [12]. Our result suggests that noise suppression for completely unknown input states is impossible except by using the bias or anisotropy of the noise itself even when one includes the ex-ante control in the scheme.…”
Section: Conclusion and Discussionmentioning
confidence: 87%
“…In addition to the above methods, Sun et al [27] firstly showed that weak measurement together with bit flip can protect the quantum entanglement from amplitude damping. Similarly, Wang et al [28] proposed a feed-forward scheme for protecting quantum state against amplitude damping. But most of the currently existing entanglement reversal (protection) schemes only can slow down the disentanglement, and the complete recovery of entanglement only occurs for the cases where the magnitude of the system decoherence, the strength of the weak measurement, and the strength of the reversing measurement satisfy a specific relation.…”
Section: Introductionmentioning
confidence: 98%
“…Fortunately, the methods of the active process have been researched, such as quantum error correction codes (from the concept of classical redundancy) 14 – 16 , dynamical decoupling controls (switching to decouple the interaction between the systems and the environment) 17 19 , and feedback controls (performing the optimal operation from the measurement result) 20 22 .…”
Section: Introductionmentioning
confidence: 99%